Effect of stitch patterns on moisture responsiveness of seamless knitted wool fabrics for activewear. Issue 2 (8th July 2020) - Gorea, Adriana; Baytar, Fatma; Sanders, Eulanda
Abstract : Purpose: The purpose of this research was to investigate the effect of knit fabric stitch patterns, as indicated by fabric thickness variations, on moisture responsiveness for different seamless knitted wool-based fabrics. Design/methodology/approach: Forty fabrics were created on a Santoni Top-2 circular knitting machine by using combinations of jersey, tuck and float stitches in combinations of wool/Nylon, wool, and spandex yarns. Physical properties of the knit fabrics as well as changes in fabric thickness during dry, wet, after 30 min air-drying and after 60 min air-drying conditions were compared. Repeated measures ANOVA tests and bivariate correlation analysis were conducted. Findings: The results indicated that changes in moisture conditions had a significant effect on fabric thickness, and these changes differed by stitch pattern groups. Float patterns and tuck/rib patterns showed a continued relaxation of fabric thickness through all conditions, but tuck stitches and rib stitches showed a thickness recovery. Wool swatches, unlike the wool/Nylon swatches, increased their average thickness in after 60 min air-drying condition compared to 30 min air-drying condition. Originality/value: This research documents the moisture responsive properties for wool based yarns, as emerging natural functional materials for seamless knitting industry, with applications in garments for activewear as well as healthcare.